Fabrication of sustainable organometallic polymeric adsorbents for remediation of fluoride from water: A novel approach. (December 2017) - Khan, Huma; Sharma, Chirag R.; Sharma, Saroj
Graphical abstract: Highlights: Organometallic crosslinked adsorbents were synthesised via suspension polymerisation. The adsorbent ZrMA5 is found to have maximum adsorption capacity of 15.2 mg/g. At neutral pH, about 96.54% removal of fluoride was achieved. The adsorbents can be regenerated and there occurs no leaching out of metal ions. The treated water remains potable for direct consumption. Abstract: In this work, we have synthesised a series of crosslinked porous polymeric adsorbents poly(zirconyl methacrylate-co-methylmethacrylate) (p(ZrDMA-co-MMA)) by polymerising the organometallic vinyl monomer via suspension polymerisation. The novel adsorbents have been investigated for defuoridation of drinking water using batch and continuous mode experiments. The effects of different parameters such as initial fluoride concentration, adsorbent dosage, pH and co-ion concentration were extensively studied to investigate the adsorption capacity in field water.The fluoride adsorption was found to be maximum at neutral pH where 96.54% fluoride removal was achieved.The equilibrium data were fitted well with Freundlich and Langmuir adsorption isotherms, and it was found that fluoride sorption on ZrMA5 followed pseudo-second order kinetics with a correlation coefficient of 0.99. Further, the adsorption kinetics was studied by both reaction based and diffusion-based models, and results indicate both the surface adsorption as well as intraparticle diffusion contributes to rate-determining step. The unique approach to incorporate zirconium metal ions into polymeric moiety in the form of the organometallic vinyl monomer has delivered safe and potable treated water by curbing the commonly encountered problem of leaching of metal ions when metal is loaded/coated/impregnated onto the polymeric moiety.